Systematic assessment of triticale‐based biorefinery strategies: sustainability assessment using multi‐criteria decision‐making (MCDM)1. (31st August 2018) - Sanaei, Shabnam; Chambost, Virginie; Stuart, Paul R
Abstract: Triticale – a hybrid of rye and wheat – is a man‐made crop that has the potential to be a preferred feedstock for the biorefinery in Canada because of its ability to grow on marginal land, its high yields, and its non‐competition with food‐based crops. However, it is challenging to identify sustainable investment options among the many possible triticale‐based biorefinery pathways. Several product‐process combinations for the production of polylactic acid (PLA) were defined in this study, each involving different degrees of technology and market risk. The different biorefinery configurations had conflicting rankings considering different criteria, making a trade‐off analysis essential to assess the most sustainable biorefinery strategies. Economic, competitive, and environmental dimensions of the biorefinery alternatives were thus evaluated in a multi‐criteria decision‐making (MCDM) panel, so that the triticale‐based biorefinery strategies could be ranked using a sustainability perspective. In this study, a set of ten criteria determined as the most important through previously‐conducted MCDMs were presented to a decision‐making panel. They determined that for PLA production, maximizing electricity production through a straw‐dedicated CHP unit was the least sustainable investment option, due to poor economic and competitiveness performance associated with its capital‐intensiveness and its failure to include a value‐added product portfolio. Therefore, this investment option was screened out from the list of strategies to be further analyzed. On the other hand, options featuring higher technology risk including energy‐efficient separation processes (ultra‐filtration) and integrated fermentation processes (SSCF) attained significantly better sustainability scores due mainly to their low energy and raw materials consumption values. © 2018 Society of Chemical Industry and John Wiley & Sons, Ltd